The effect of using theodolite 3D AR in teaching measurement error on learning outcomes and satisfaction of civil engineering students with different spatial ability - Weng, Cathy; Puspitasari, Dani; Tran, Khanh Nguyen Phuong; Feng, Pei Jie; Awuor, Nicholas O.; Matere, Isaac Manyonge (Interactive learning environments, 2023)
The purpose of this study was to investigate the effect of augmented reality (AR) using a 3D app in a smartphone on students' learning outcomes and satisfaction in teaching angle measurement error to vocational high school students with different spatial ability. A quasi-experimental pretest/posttest was employed. There were 197 students from three vocational high schools in the southern, northern, and eastern part of Taiwan participated in this study. To minimize the biased result, we established one control group and one experimental group in each school. The experimental group used multimedia teaching tools and AR technology as a supplement, while the control group was taught by multimedia teaching tools only. We assessed some factors that possibly affect the learning outcomes and learning satisfaction, including different spatial abilities and different digital materials as teaching tools. Our finding highlights that different teaching materials influence students' learning outcomes and satisfaction, whereas spatial ability does not affect. Further discussion and implementation are also identified in this study.